INNOVATIVE PEDAGOGICAL APPROACHES TO DEVELOPING MEDIA COMPETENCE OF FUTURE TEACHERS IN THE DIGITAL AGE - Yuldashov Sherzod Sattorovich (Modern American Journals, 2025)
This article analyzes the processes of corporate strategy formation in building materials manufacturing enterprises based on scientific and practical approaches. The study examines the interrelationship of micromarkets, production strategy, innovative technologies, and sustainability principles. International experiences, including strategies of large companies, are compared with the possibilities of application in national conditions. The results show that a comprehensive strategy based on market signals, production decisions, and environmental requirements increases the long-term competitiveness and economic efficiency of enterprises.
Keywords: corporate strategy, building materials, micromarket, production efficiency, sustainability, innovation, ESG